Stress response leading to resistance in glioblastoma- The need for innovative radiotherapy (iRT) concepts - Combs, Stephanie E.; Schmid, Thomas E.; Vaupel, Peter; Multhoff, Gabriele (Cancers, 2016)
Glioblastoma (GBM) is the most common and most aggressive malignant primary brain tumor in adults. In spite of multimodal therapy concepts, consisting of surgery, radiotherapy and chemotherapy, the median survival, merely 15–18 months, is still poor. Mechanisms for resistance of GBM to radio(chemo)therapy are not fully understood yet and due to the genetic heterogeneity within the tumor including radiation-resistant tumor stem cells, there are several factors leading to therapy failure. Recent research revealed that, hypoxia during radiation and miRNAs may adversely affect the therapeutic response to radiotherapy. Further molecular alterations and prognostic markers like the DNA-repair protein O6-methylguanine-DNA methyltransferase (MGMT), anti-apoptotic molecular chaperones, and/or the activity of aldehyde dehydrogenase 1 (ALDH1) have also been identified to play a role in the sensitivity to cytostatic agents. Latest approaches in the field of radiotherapy to use particle irradiation or dose escalation strategies including modern molecular imaging, however, need further evaluation with regard to long-term outcome. In this review we focus on current information about the mechanisms and markers that mediate resistance to radio(chemo)therapy, and discuss the opportunities of Innovative Radiotherapy (iRT) concepts to improve treatment options for GBM patients.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Glioblastoma; Hypoxia; Imaging; Immune system; Particle therapy; Radiation